(untitled) (European Journal of Pure and Applied Mathematics, 2025)
The main focus of the current study is to present a detailed review the impact of physical and thermal properties of thermophoretic convective heat transfer in different fluids by taking insight from the previous literature or published research. Further, the second aim is to provide a strong ground of study for scholars, researchers and scientists those are working in this field through detailed literature review. The main source of thermophoretic particles is the fossil fuels that released the thermophoretic particles such as carbon dioxide , methane , Black Carbon and many others. Since the thermophoresis particles are acidic and submicron in size, they can contribute to climate change by altering weather patterns and raising atmospheric temperatures. This study will give a clear insight to the researchers how the classical research is important to establish new theories and innovations in the field of thermal fluid science. It is important to point out that the thermophoretic heat transfer is a phenomenon in which very small particles move away from the hot surface or come towards the cold surface due to the temperature gradient. Numerous applications of the thermophoresis mechanism can be found in the natural sciences and engineering, including the recently growing problem of climate change. The main novelty of the current review is to discuss the combined characteristics of thermophoretic particles for different aspect of heat and mass transfer issues along different geometries. This study highlights the importance of these tiny/small particles in newly emerging issue of global warming in current literature. Additionally, the introduction section provides a thorough explanation of several elements of the thermophoresis particle’s features based on information gathered from the literature.